The Perils and Pitfalls of Esophageal Dysmotility in Idiopathic Pulmonary Fibrosis. (9th June 2021) - Cheah, Ramsah; Chirnaksorn, Supphamat; Abdelrahim, Ahmed H.; Horgan, Laura; Capstick, Toby; Casey, John; Peckham, Daniel; Boland, Alison; Sutherland, Timothy J. T.; Beirne, Paul; Lee, Augustine S.; DeVault, Kenneth R.; et al.
Abstract : INTRODUCTION: Gastroesophageal reflux plays a significant role in idiopathic pulmonary fibrosis (IPF). Given the morbidity and mortality associated with IPF, understanding the mechanisms responsible for reflux is essential if patients are to receive optimal treatment and management, especially given the lack of clear benefit of antireflux therapies. Our aim was to understand the inter-relationships between esophageal motility, lung mechanics and reflux (particularly proximal reflux—a prerequisite of aspiration), and pulmonary function in patients with IPF. METHODS: We prospectively recruited 35 patients with IPF (aged 53–75 years; 27 men) who underwent high-resolution impedance manometry and 24-hour pH-impedance, together with pulmonary function assessment. RESULTS: Twenty-two patients (63%) exhibited dysmotility, 16 (73%) exhibited ineffective esophageal motility (IEM), and 6 (27%) exhibited esophagogastric junction outflow obstruction. Patients with IEM had more severe pulmonary disease (% forced vital capacity: P = 0.032) and more proximal reflux ( P = 0.074) than patients with normal motility. In patients with IEM, intrathoracic pressure inversely correlated with the number of proximal events (r = −0.429; P = 0.098). Surprisingly, inspiratory lower esophageal sphincter pressure (LESP) positively correlated with the percentage of reflux events reaching the proximal esophagus (r = 0.583; P = 0.018), whereas in patients with normal motility, it inversely correlated with the bolus exposure time (r = −0.478; P = 0.098) and number of proximal events (r = −0.542; P = 0.056). % forced vital capacity in patients with IEM inversely correlated with the percentage of reflux events reaching the proximal esophagus (r = −0.520; P = 0.039) and inspiratory LESP (r = −0.477; P = 0.062) and positively correlated with intrathoracic pressure (r = 0.633; P = 0.008). DISCUSSION: We have shown that pulmonary function is worse in patients with IEM which is associated with more proximal reflux events, the latter correlating with lower intrathoracic pressures and higher LESPs.